2018
DOI: 10.1007/s10578-018-0817-5
|View full text |Cite
|
Sign up to set email alerts
|

Open Trial of Modular Cognitive-Behavioral Therapy in the Treatment of Anxiety Among Late Adolescents with Autism Spectrum Disorder

Abstract: Given the high rates of comorbid anxiety and autism spectrum disorder (ASD) in the adolescent and young adult population, effective treatment protocols to address anxiety symptoms are of importance to help promote greater independence across settings. While research supports the use of cognitive-behavioral therapy (CBT) across younger age groups with ASD, the literature is limited on interventions benefitting adolescents and young adults with comorbid anxiety disorders and ASD. Therefore, this open trial utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 45 publications
0
18
0
1
Order By: Relevance
“…CBTs were previously reported as useful in improving functioning among typically developing students with social phobia [Tillfors et al, ]. Recent randomized controlled studies have also indicated positive effects of CBT on reduction of anxiety symptoms among individuals with ASD [Murphy et al, ; Reaven et al, ; Wise et al, ]. However, most of these studies were conducted with children or adolescents, focused on reduction of different kinds of anxiety, and used generic CBT protocols not specifically designed for treatment of social anxiety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CBTs were previously reported as useful in improving functioning among typically developing students with social phobia [Tillfors et al, ]. Recent randomized controlled studies have also indicated positive effects of CBT on reduction of anxiety symptoms among individuals with ASD [Murphy et al, ; Reaven et al, ; Wise et al, ]. However, most of these studies were conducted with children or adolescents, focused on reduction of different kinds of anxiety, and used generic CBT protocols not specifically designed for treatment of social anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, high levels of social anxiety symptoms may result in a diagnosis of social anxiety disorder (SAD), also known as social phobia [Diagnostic and Statistical Manual of Mental Disorders (DSM‐5), APA, ]. Although the high prevalence of anxiety disorders among individuals with ASD has led to studies utilizing cognitive behavioral therapy [CBT; Murphy et al, ; Reaven et al, ; Wise et al, ], most have been conducted with children or adolescents, and have used general CBT protocols not specifically designed for addressing social anxiety. As social anxiety may significantly affect the ability to adapt to everyday independent functioning among students without and with ASD [Kraper, Kenworthy, Popal, Martin, & Wallance, ], remedying this gap in adult ASD research is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…The field of implementation science has evolved to help bridge this gap and to better understand the barriers and facilitators that exist in translating evidence-based innovations into practice such that successful efficacy trials do become eventual successful effectiveness trials where interventions are delivered with fidelity in an economical and sustainable way in the community worldwide (Wood, McLeod, et al, 2015). In our review, about half of the efficacy studies identified (Ehrenreich-May et al, 2014; Fujii et al, 2013; Reaven et al, 2012b; Storch et al, 2013; Vause et al, 2017; Weiss et al, 2015; White et al, 2013; Wood et al, 2009; Wood, Ehrenreich-May, et al, 2015) went on to become eventual effectiveness studies (Ames & Weiss, 2013; Beidas et al, 2010; Floor & Lane, 2018; Guertin et al, 2019; Ireri et al, 2019; Kester & Lucyshyn, 2019; Wise et al, 2019; Wood et al, 2014). These studies occurred using a number of different CBT programs (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…La literatura científica principalmente demuestra su práctica para intervenir los síntomas específicos, adoptando técnicas dirigidas a mejorar las habilidades de comunicación y afrontamiento, entrenamiento en la atención y comportamiento, capacitación a los padres, entre otros. La presencia simultánea de problemas psicológicos también es abordada, donde mayormente se evidencia la intervención en los síntomas depresivos o de ansiedad (Wise et al, 2019). No obstante, la evidencia de intervenciones en comportamientos suicidas es bastante limitada.…”
Section: Intervenciones Psicológicas Basadas En Evidenciaunclassified